Gender differences in corporate hierarchies - Antti Kauhanen (IZA World of Labor, 2022)
The gender wage gap is largely due to men and women holding different kinds of jobs. This job segregation is partly driven by gender differences in careers in corporate hierarchies. Research has shown that the careers of men and women begin to diverge immediately upon entry into the labor market and that subsequent career progress exacerbates the divergence. This divergence of career progress explains a large part of the gender wage gap. Understanding how and why the careers of men and women differ is necessary to design effective policies that can reduce the gender differences in hierarchies.
Keywords: J16; J24; J31; J62; 330; promotions; gender wage gap; job assignment